2018
DOI: 10.1016/j.dib.2018.03.126
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of small and medium enterprises to economic development: Evidence from a transiting economy

Abstract: The focus of this research was to present a data article on the contribution of SMEs to economic development in a transiting economy. Descriptive research design was adopted in this study. Data were obtained from 600 respondents in 60 small-scale enterprises located in different parts of the country (20 small-scale enterprises located in Lagos State, 20 in Anambra State and 20 in Kano State of Nigeria respectively). Data analysis was carried out using tables and percentages and the null hypotheses of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 2 publications
(1 reference statement)
1
55
0
1
Order By: Relevance
“…Small and medium enterprises (SMEs) are a noteworthy driver of economic development [1], being vital to most economies across the world, particularly in developing and emerging nations [2]. They represent 99% of all businesses in the European Union (EU) and in the last five years, provided about 85% of new jobs, also ensuring two-thirds of the total private sector engagement in the region [3].…”
Section: Introductionmentioning
confidence: 99%
“…Small and medium enterprises (SMEs) are a noteworthy driver of economic development [1], being vital to most economies across the world, particularly in developing and emerging nations [2]. They represent 99% of all businesses in the European Union (EU) and in the last five years, provided about 85% of new jobs, also ensuring two-thirds of the total private sector engagement in the region [3].…”
Section: Introductionmentioning
confidence: 99%
“…SMEs is one of business type which have greatly contributed in economic development. In several recent researches, it is found that SMEs serve as the significant drivers of the economic development and SMEs also identified could take many important roles in economic aspects (Obi et al, 2018) like SMEs could fundamentally support the job creation, SMEs could significantly impact to the povertyalleviation through providing some job opportunities to the unemployment (Okpara and Wynn, 2007) and SMEs could significantly contribute to the improvement of the living standard.…”
Section: A Small and Medium Enterprises (Smes)mentioning
confidence: 99%
“…Good education in entrepreneurial skills could drive sustainable performance and growth of small-medium enterprises. Henceforth, small-medium enterprises contribute significantly to the development of an economic nation (Obi et al, 2018).…”
Section: General Evaluationmentioning
confidence: 99%
“…Start-up businesses have the potential to decrease unemployment among graduates through innovation and job creation (Lukes, Longo, and Zouhar, 2019). In addition, micro and small enterprises contribute to the development of an economic nation (Obi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%